Seismic risk to beam end corner in railway bridges. (January 2023) - Huang, Wei; Deng, Kailai; Huang, Yuanyuan; Zhan, Yulin; Mou, Tingmin
Abstract: The beam end of the railway bridge is the crucial part of the whole bridge, and the earthquake will cause damage to the beam end. In order to ensure the safety of the bridge and track system. To investigate the risk of seismic deformations at the beam end in railway bridges, a three-span continuous rigid frame bridge was taken as a case study and a three-dimensional finite element model of the whole bridge was established in ABAQUS. The deformation angle of the beam end was selected as the damage index, and the seismic vulnerability and risk curves of the beam end were calculated by the incremental dynamic analysis (IDA) method using 22 scaled ground motion time histories. The results show that in the same range of peak ground accelerations (PGAs), the influence of cross-bridge ground motion on the corner deformations of the beam end was much greater than that of the along-bridge ground motion. Under the along-bridge seismic excitation, the damage probabilities for the rotation angles in X, Y and Z-directions did not exceed 50 %. In different damage states, increasing in PGA correlated positively with the beam end damage probability. The vulnerability curves for PGA can be used for the seismic risk assessment of the beam end and can also provide decision support for prioritizing the seismic reinforcement of bridges.